RURAL FLASH-FLOOD BEHAVIOR IN GOUYAVE WATERSHED, GRENADA, CARIBBEAN ISLAND - Rahmat Aris Pratomo; Victor Jetten; Dinand Alkema (Geoplanning: Journal of Geomatics and Planning, 2016)
Flash-flood is considered as one of the most common natural disasters in Grenada, a tropical small state island in Caribbean Island. Grenada has several areas which are susceptible to flooding. One of them is Gouyave town which is located in the north-west of Grenada. Its land-use types are highly dominated by green areas, especially in the upper-part of the region. The built-up areas can only be found in the lower-part of Gouyave watershed, near the coastal area. However, there were many land conversions from natural land-use types into built-up areas in the upper-part region. They affected the decrease of water infiltration and the increase of potential run-off, making these areas susceptible to flash-flood. In addition, it is also influenced by the phenomenon of climate change. Changes in extreme temperature increase higher potential of hurricanes or wind-storm, directly related to the potential escalation of flash-flood. To develop effective mitigation strategies, understanding the behavior of flash-flood is required. The purpose of this paper was to observe the behavior of flash-flood in Gouyave watershed in various return periods using OpenLISEM software. It was used to develop and analyse the flash-flood characteristics. The result showed that the climatic condition (rainfall intensity) and land-use are influential to the flash-flood event. Flash-flood occurs in 35 and 100 years return period. Flash-flood inundates Gouyave’s area in long duration, with below 1 m flood depth. The flood propagation time is slow. This condition is also influenced by the narrower and longer of Gouyave basin shape. To develop flash-flood reduction strategies, the overall understanding of flash-flood behavior is important. If the mitigation strategy is adapted to their behavior, the implementation will be more optimum.